ESTRÉS ACADÉMICO Y SALUD MENTAL EN ESTUDIANTES DE SÉPTIMO Y OCTAVO SEMESTRE DE LA CARRERA DE PSICOLOGÍA DE LA UNIVERSIDAD TÉCNICA DE BABAHOYO - ESPINOZA CHACON EMELYTH VALENTINA (2024)
Stress is one of the most widespread health problems today, resulting from the relationship between the person and the events of their environment, which jeopardize their well-being. In spite of this, in students it is a natural reaction to the various demands and requirements of the university. On the other hand, mental health is the physical, psychological and social wellbeing that allows coping with stress, developing skills and contributing to the community. Thus, it can be revealed that there are different types of stress: acute stress, acute-episodic stress, and chronic stress, as well as various causes of stress, such as personal demands, competitiveness, meeting expectations, comparisons, lack of organization and planning; it is related to mental health so that a good education at home and school, helps the person to be fully formed to self-realize and contribute to society, expanding all areas of the human being, especially education as primary prevention. Therefore, with the above described, the interest was born to define the incidence of academic stress in the mental health of university students; and to be able to do so, in the first instance the main risk factors of academic stress were described by means of the SISCO SV-21 inventory, and then to evaluate mental health with the GHQ-28 questionnaire. These measurement instruments for data collection were applied to 80 university students who are part of the seventh and eighth semesters of the Technical University of Babahoyo. This study was carried out by means of descriptive research